FARMERS’ FIELD SCHOOLS: A STRATEGY FOR BENIFITING RESOURCE POOR FARMERS IN KHYBER PAKHTUNKHWA, PAKISTAN - A. Khatam; S. Muhammad; I. Ashraf (Journal of Animal and Plant Sciences, 2013)
The present paper is based on the study conducted in 2010 to analyze farmers’ field schools (FFS) as a strategy for benefiting resource poor farmers from agricultural technologies in Khyber Pakhtunkhwa, Pakistan. For this purpose, seven districts from Khyber Pakhtunkhwa including Peshawar, Charsadda, Nowshera, Mardan, Swabi, Kohat and Hangu were selected. Data were obtained from 280 randomly selected farmers through “survey” method and were analyzed using statistical package for social sciences (SPSS). The results show that under crop production technologies, the highest benefit was obtained from nursery raising which was ranked 1st with mean value 3.40 followed by timely and balanced use of fertilizers and use of recommended seed rate which were ranked 2nd and 3rd with mean values 3.08 and 3.05, respectively. Under crop protection farmers got maximum benefits from iidentification of insects/ pests which was ranked 1st with mean value 3.22 followed by insects/ pests control by local recipes and mass killing of insect/ pests which were ranked 2nd and 3rd with mean values 3.03 and 2.84, respectively. The farmers obtained the highest benefits from chemical and manual weed control measures which were ranked 1st and 2nd with mean values 2.99 and 2.97, respectively. Furrow irrigation was ranked at the top followed by flood and border irrigation techniques based on the benefits. It can be concluded from the study that FFS proved highly beneficial to the farming community due to its capacity building functions.
Keywords: Farmers’ field schools; benefits; resource-poor-farmers